Tanatosemiosis: communication with deceased children. Tombs, colors, epitaphs, votive offerings and memories - Bondar, César Iván (2012)
The term tanatosemiosis stems from our critical approaches to productions on communication with the deceased (mainly Finol and Fernández, 1996, Finol and Finol, 2009 and Bernal Botero, 2010). These ideas will be used to analyze the problematic of deceased children (angelitos or “little angels”) in two chronotopic specificities: the public cemeteries of Corrientes Province in Argentina and the remembrance of dead children in the Community of Villa Olivari (Corrientes). The funerary practices regarding children are considered especially distinct to those of adults. The remembrance, the tombs, the epitaphs and the votive offerings form not only specific interpretative, symbolic and subjective schemes, but also communicative logics strongly rooted in what Finol and Fernández (1996) called the “semiotics of feminine”. These communicational frameworks, like symbolic configurations, (re) appear in the rituals, colors, tombs, epitaphs and votive offerings; constituting specific tanatosemiotic systems of beliefs-habits. The methodology used draws from transdisciplinary contributions from Anthropology, Communication and Semiotics. The analyzed corpus was constructed on the base of first-hand data collected between 2005 and 2010.